2010
DOI: 10.1364/oe.18.012852
|View full text |Cite
|
Sign up to set email alerts
|

Broadband NIR photoluminescence from Bi-doped Ba_2P_2O_7 crystals: Insights into the nature of NIR-emitting Bismuth centers

Abstract: We report on a novel type of Bi-doped crystal that exhibits ultrabroadband photoluminescence in the near infrared (NIR). Emission centers can be generated and degenerated reversibly by annealing the material in CO atmosphere and air, respectively, indicating that emission is related to the presence of Bi-species in low valence states. Correlating static and dynamic excitation and emission data with the size and charge of available lattice sites suggests that two types of Bi(0)-species, each located on one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 51 publications
3
90
0
Order By: Relevance
“…The combined experimental evidence of XRD and PL 5 results, taken in conjunction with the result of quantum chemistry calculation, makes it clear that both Bi 8 2+ and Bi 5 3+ contribute to the observed NIR emission. Furthermore, it was revealed that Bi 8 2+ polycation where Bi has an average oxidation state of + 0.25 results in the emission peaking at around 1180 nm, while 10 Bi 5 3+ the longer-wavelength emission. It is clear that systematical examination of structural and luminescent properties as well as detailed quantum chemistry calculation of molecular crystals containing such kinds of bismuth units allows us to obtain a deeper understanding on bismuth-related photophysical behaviors, 15 because of the establishment of structure-property relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined experimental evidence of XRD and PL 5 results, taken in conjunction with the result of quantum chemistry calculation, makes it clear that both Bi 8 2+ and Bi 5 3+ contribute to the observed NIR emission. Furthermore, it was revealed that Bi 8 2+ polycation where Bi has an average oxidation state of + 0.25 results in the emission peaking at around 1180 nm, while 10 Bi 5 3+ the longer-wavelength emission. It is clear that systematical examination of structural and luminescent properties as well as detailed quantum chemistry calculation of molecular crystals containing such kinds of bismuth units allows us to obtain a deeper understanding on bismuth-related photophysical behaviors, 15 because of the establishment of structure-property relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The sample was grounded into powders, sealed in 1 mm Hilgenberg borosilicate capillaries and kept spinning during the measurement. The EEM was taken by 10 Horiba NanoLog spectrofluorometer equipped with a monochromated Xe lamp and a liquid N 2 cooled photomultiplier tube (Hamamatsu, R5509-72). The powder was sandwiched between a glass microscope slide and a quartz cover glass and sealed with glue.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…For example, decreasing the redox state of bismuth towards the formation of metallic nanoparticles has been known as an easy method to tune glass color from yellow to reddish tints to deep black [15]. To prevent the formation of lower-valence bismuth states during glass fabrication, several methods have been explored, such as calcination of the precursors, different annealing temperatures, shorter melting times and the use of different crucible materials [2,16,17]. Another possibility to prevent reduction is through oxidants, MeO x , which provide oxygen to the glass system while the cation is embedded in the network.…”
Section: Introductionmentioning
confidence: 99%
“…The Bi 3+ ion in the common oxidation state +3 has no optical transitions in NIR and the observed emission was attributed to possible Bi 5+ , 1 Bi 2+ , 20 Bi + , 21 Bi 0 , 8,9,22 Bi 2 À , Bi 2 2À , 23 and bismuth cluster species. 24 The related information was also summarized in the recent review.…”
Section: Introductionmentioning
confidence: 97%